Marshall McLuhan : un spectre hante-t-il les études médiévales canadiennes ? - Patrick Moran (Perspectives Médiévales, 2016)
This article is an examination of Marshall McLuhan’s work and of its pervasive influence on Medieval Studies in Canada and beyond. The media-based paradigm developed by McLuhan allows him, in The Gutenberg Galaxy, to depict the Middle Ages as a transitional period, a composite civilization that tends towards the massive domination of visual media and the invention of print, but still retains a foothold in the earlier media environment of the ear and of synaesthesia. The article examines the heuristic value of McLuhan’s theses as well as their influence on the medievalist discourse in Canada, from Paul Zumthor’s critical reception in the early eighties to current approaches based on the philological and codicological renewal of the late twentieth and early twenty-first centuries.